Permanent tooth eruption based on chronological age and gender in 6-12-year old children on Madura - Agus Marjianto; Mieke Sylvia; Soegeng Wahluyo (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Tooth eruption, the movement of teeth toward the oral cavity clinically marked by the emergence of the cusp or incisal edge, is very important in determining the chronological age of a child. Unfortunately, tooth eruption in 6-12-year olds on the island of Madura has yet to be investigated. Purpose: This study aimed to analyze differences in permanent tooth eruption between boys and girls aged 6 to 12 years old on Madura. Methods: This study employed an observational analytic design in combination with a cross-sectional approach. The samples used in this study were selected by means of simple random sampling technique. Post-selection informed consent of the child subjects was obtained with their chronological age being assessed and determined prior to tooth eruption. The normality of the data was subsequently analyzed by application of a one sample non-parametric Kolmogorov Smirnov test. Thereafter, repeated Anova tests were conducted to determine differences in the permanent tooth eruption of the subjects. Results: Based on the normality test results, the significance value of the permanent maxillary teeth in the male subjects was 0.993, while that of their permanent mandibular teeth was 0.695. In contrast, the significance value of the permanent maxillary teeth in the female subjects was 0.970, while that of their permanent mandibular teeth was 0.918. According to the results of the repeated measure ANOVA test, differences existed in the eruption of the permanent maxillary and mandibular teeth between the males and females with a significance value (ρ) of 0.020. The mean value of permanent mandibular tooth eruption in the females was 56.59 ± SD 33.403, while that of their permanent maxillary tooth eruption was 50.77 ± SD 34.201. The mean value of the permanent mandibular tooth eruption in the males was 55.31 ± 33.024, while that of their permanent maxillary tooth eruption was 48.77 ± SD 34.201. Conclusion: On Madura, the permanent teeth of chronological 6-12-year old females, particularly their permanent mandibular canine teeth, erupt earlier than those of their male counterparts.